2013
DOI: 10.1159/000355344
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Occupational Risk Factors for Amyotrophic Lateral Sclerosis: A Case-Control Study

Abstract: Background/Aims: Environmental and occupational exposures are implicated as risk factors for amyotrophic lateral sclerosis (ALS), the etiology of which is largely unknown, although no causal relationships have been established. Objective: The aim of the study was to evaluate the associations of personal risk factors and self-reported environmental and occupational exposures with risk of ALS. Methods: The cases involved ALS patients (n = 66) identified from major neurological centers in Pittsburgh and Philadelp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 33 publications
4
40
1
1
Order By: Relevance
“…Here we report an association with aromatic solvents that was not observed in our prior investigation of environmental and occupational exposures. Associations between occupational exposure to metals and pesticides and an increased risk of ALS, after adjustment for smoking, education, and other exposure groups were reported by our previous study (Malek et al, 2014). Possible mechanisms for the observed association between ambient air concentrations of aromatic solvents and the risk of ALS include peripheral neuropathy (Gobba et al, 1995) or autonomic nervous system activity dysfunction (Murata et al, 1991;Beck et al, 2005).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Here we report an association with aromatic solvents that was not observed in our prior investigation of environmental and occupational exposures. Associations between occupational exposure to metals and pesticides and an increased risk of ALS, after adjustment for smoking, education, and other exposure groups were reported by our previous study (Malek et al, 2014). Possible mechanisms for the observed association between ambient air concentrations of aromatic solvents and the risk of ALS include peripheral neuropathy (Gobba et al, 1995) or autonomic nervous system activity dysfunction (Murata et al, 1991;Beck et al, 2005).…”
Section: Discussionsupporting
confidence: 64%
“…One study also included a panel of industrial hygienists (McGuire et al, 1997). Some studies have reported a significant association between exposure to solvents or occupations involving solvent exposure and ALS or MND (Morahan and Pamphlett, 2006;Chio et al, 1991;Chancellor et al, 1993;Graham et al, 1997;Park et al, 2005;Pamphlett, 2012), while others have not (Malek et al, 2014;McGuire et al, 1997;Fang et al, 2009;Gunnarsson et al, 1992;Hawkes and Fox, 1981;Gait et al, 2003;Strickland et al, 1996;Savettieri et al, 1991;Granieri et al, 1988;Welp et al, 1996;Gunnarsson et al, 1991). Two studies reported increased mortality from MND among leather workers (Hawkes and Fox, 1981;Buckley et al, 1983), but another did not find this association (Gunnarsson and Lindberg, 1989;Martyn, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent study, conducted after the meta-analyses, showed no elevated risk of ALS mortality and exposure to pesticides but did show increased risks for several specific pesticides, including exposure to aldrin and dieldrin 14. Malek et al 36 and Yu et al 43 also showed an association between occupational exposure to pesticides and ALS incidence. We found a non-significant, negative association between occupational exposure to pesticides, herbicides or insecticides and ALS mortality.…”
Section: Discussionmentioning
confidence: 95%
“…Assignment of specific metals based on a JEM is difficult, as occupational categories are generally too broad to distinguish between exposures to specific metals. Some studies have found an association between occupational exposure to metals and ALS mortality using this methodology,36 although others did not 43. We used the ALOHA+-JEM to assign total metal exposure, which due to the broad categorisation might not have captured possible associations between specific metals and ALS mortality.…”
Section: Discussionmentioning
confidence: 99%